Predictive maintenance scheduling with reliability characteristics depending on the phase of the machine life cycle. Issue 1 (2nd January 2021) - Paprocka, Iwona; Kempa, Wojciech M.; Skołud, Bożena
Abstract : The method of maintenance and production task scheduling is proposed to make the production system insensitive to a disruption. The method enables the maintenance of high values of schedule evaluation indicators in variable conditions, such as stability robustness and quality robustness. The frequency of a machine failure is described by the Maxwell distribution. Formulae for different reliability characteristics are given. The parameters of the distribution are estimated using maximum likelihood, empirical moments and a method based on the renewal theory. The advantage of the last method is the ability to achieve accurate predictions of failure-free time of a machine, when there is a lack of complementary and reliable historical data. In the related literature, only the first method is used to estimate unknown parameters of the probability distribution. The methods are applied to job-shop scheduling problems to evaluate their impact on achieving predictive schedules.